Adopting agile practices when developing software for use in the medical domain. Issue 5 (23rd July 2013) - McHugh, Martin; McCaffery, Fergal; Casey, Valentine; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
SUMMARY Non‐safety critical software developers have been reaping the benefits of adopting agile practices for a number of years. However, developers of safety critical software often have concerns about adopting agile practices. Through performing a literature review, this research has identified the perceived barriers to following agile practices when developing medical device software. A questionnaire‐based survey was also conducted with medical device software developers in Ireland to determine the barriers to adopting agile practices. The survey revealed that half of the respondents develop software in accordance with a plan‐driven software development lifecycle and that they believe that there are a number of perceived barriers to adopting agile practices when developing regulatory compliant software such as being contradictory to regulatory requirements, insufficient coverage of risk management activities and the lack of up‐front planning. In addition, a comparison is performed between the perceived and actual barriers. Based upon the findings of the literature review and survey, it emerged that no external barriers exist to adopting agile practices when developing medical device software and the barriers that do exists are internal barriers such as getting stakeholder buy in. Copyright © 2013 John Wiley & Sons, Ltd.